2006
DOI: 10.1007/s10353-006-0251-y
|View full text |Cite
|
Sign up to set email alerts
|

Video-endoscopy for evaluation of columnar lined esophagus in patients with gastroesophageal reflux disease

Abstract: Zusammenfassung. Grundlagen: Angabe der Biopsielokalisation (Ösophagus vs. Magen) ist notwendig, um die histologische Diagnose von Reflux-assoziierten Verän-derungen am Übergang Ösophagus/Magen zu erstellen. Wir haben den Wert der Videoendoskopie für die Diagnostik am ösophagogastralen Übergang untersucht.Methodik: 29 konsekutive Patienten (m:w = 17:12) mit gastroösophagealer Refluxkrankheit (GERD) wurden prospektiv endoskopiert (EGD). EGD und Biopsien wurden digital aufgezeichnet und danach analysiert. Nach i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
1

Year Published

2006
2006
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(54 citation statements)
references
References 34 publications
2
51
0
1
Order By: Relevance
“…absence or presence of visible tongues of gastric-type mucosa above the level of the start of the rugal folds) [1,7,8,20]. Accordingly, Lenglinger et al [21] recently found that none of the biopsies obtained from a normal-appearing endoscopic esophagogastric junction contained direct transition from squamous epithelium to oxyntic mucosa. Thus, it is debatable whether the start of the gastric folds is an adequate landmark for defining the esophagogastric junction and whether the junction can be identified by endoscopy.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…absence or presence of visible tongues of gastric-type mucosa above the level of the start of the rugal folds) [1,7,8,20]. Accordingly, Lenglinger et al [21] recently found that none of the biopsies obtained from a normal-appearing endoscopic esophagogastric junction contained direct transition from squamous epithelium to oxyntic mucosa. Thus, it is debatable whether the start of the gastric folds is an adequate landmark for defining the esophagogastric junction and whether the junction can be identified by endoscopy.…”
Section: Introductionmentioning
confidence: 94%
“…CLE with IM had been detected in a previous endoscopy). These five patients were part of a recent endoscopy study [21] that included biopsies from the endoscopically visible start of the gastric folds and any visible segment of gastric-type mucosa in the esophagus above this level. In contrast to the present study, biopsies were not obtained distal to the rise of the gastric folds [21].…”
Section: Study Protocolmentioning
confidence: 99%
See 3 more Smart Citations